1997
DOI: 10.1111/j.1442-200x.1997.tb03594.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of Japanese children and adolescents with systemic lupus erythematosus: Results of 1980–1994 survey

Abstract: Marked advances have been made in the past decade in the management of adults with systemic lupus erythematosus (SLE). Therefore, a nationwide retrospective survey was conducted between 1980 and 1994 to investigate the clinical manifestations of SLE in Japanese children and adolescents. Questionnaires were sent to 340 hospitals. Of 405 patients reported by 176 hospitals, 373 patients, diagnosed by the criteria established by the Pediatric Study Group of the Japanese Ministry of Health and Welfare in 1985, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 7 publications
2
23
2
Order By: Relevance
“…Alsalloum et al [40] reported that mean AI was 8.2 (range 0. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] in Saudi LN children with class III and IV disease. In the study of Bogdanovic et al [28], AI was 9 (range 2-14) in patients with class IV LN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alsalloum et al [40] reported that mean AI was 8.2 (range 0. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] in Saudi LN children with class III and IV disease. In the study of Bogdanovic et al [28], AI was 9 (range 2-14) in patients with class IV LN.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have described the features of childhood SLE among different ethnic and geographical groups [6,7,8,9,10,11,12]. Studies of SLE among Arab children are few [13,14,15,16], and there is only one study of Egyptian children [17].…”
Section: Introductionmentioning
confidence: 99%
“…Three of them (one boy (9), two girls (8, 10)) had become negative again by the time of the third investigation. One girl became positive at 14 years old (12). One boy was positive at 5 years of age and had become negative by 11 years of age (11).…”
Section: Discussionmentioning
confidence: 98%
“…This ratio is similar to those demonstrated in familial cases of SLE and SLE in childhood. 12 This discrepancy between the sexes might be considered as due to hormonal, environmental, behavioural, or genetic effects. Hormonal effects must exclude oestrogen because serum oestrogen levels are the same for boys and girls.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Additionally, in Japan, we have applied those therapies even in cases complicated only with hypocomplementemia, because this condition reflects the disease activity in childhood SLE. 16 In the past, the goals of long-term management in patients with SLE were to suppress the disease activity with a minimum of side effects, and to improve the quality of life in patients with SLE. However, ultimately, it is of course our wish that such patients can, if possible, live without medication.…”
Section: Discussionmentioning
confidence: 99%